Drivers of teachers' pedagogical competence in the digital era: A meta-analysis of educational technology integration, organizational support, and self-efficacy - Khotimah, Khusnul; Djatmika, Ery Tri; Utaya, Sugeng; Atmoko, Adi (Journal of Interdisciplinary Studies in Education, 2026)
This meta-analysis examines the drivers of teachers' pedagogical competence in the digital era, focusing on educational technology integration, organizational support, and self-efficacy. Following PRISMA 2020 guidelines, we analyzed 105 peer-reviewed studies (2016–2026) from Scopus and Web of Science. Results revealed significant positive effects: technology integration interventions showed large effects on TPACK development (d = 0.839); IT self-efficacy strongly correlated with TPACK (r = 0.607); and the Technology Acceptance Model explained 39.2% of variance in adoption intentions. Pre-service teachers exhibited stronger self-efficacy–TPACK correlations (r = 0.666) than in-service teachers (r = 0.538). Methodological gaps included limited longitudinal designs and geographic concentration. Findings suggest effective pedagogical competence development requires integrated approaches combining technology literacy, institutional support, and self-efficacy enhancement within context-sensitive frameworks.